Budidaya Tanaman Nanas dalam upaya Meningkatkan Nilai Ekonomi Pondok Pesantren - Puji Rahayu; Nita Zakiah; Aida Rohmah; Khairul Anwar; M. Sayyidul Abrori (CV. Creative Tugu Pena, 2023)
The curriculum that established at Islamic Boarding Schools was prepared by combining religious education as a provision of religious knowledge and general knowledge. The purpose of this assistance was to cultivate pineapple plants to increase the economic value of Islamic boarding schools. Researchers used Community Based Research (CBR). This activity was carried out at Miftahul Jannah Islamic Boarding School, Kalicinta, North Kotabumi, North Lampung. The sample was 30 participants. The method used in carrying out the activities involve conducting interviews with the administrators of the Miftahul Jannah Islamic Boarding School, North Kotabumi, North Lampung. The activities were conducting counseling and training on the optimization of land, distribution and selection of pineapple seeds and manure, implementation of yard land optimization activities, and monitoring and evaluation of land optimization activities. This finding helped Islamic boarding schools in optimizing empty yards into productive land. Hence, in the future it could help increase the economic value or income of the boarding school, so that it makes economic independence for Islamic boarding schools. Keywords: Pineapple Cultivation, Economic Improvement, Increasing Economic Pesantren